Environmental Valuation of the Julantoro Reservoir, in Bantul Regency - Budiman, Puput Wahyu (ReTII, 2021)
Embung is an important water resource infrastructure and functions as a water reserve and habitat for various types of freshwater biota. The changes in land using around the Embung Julantoro area have resulted in sedimentation and pollution of the reservoir, which has reduced the function of the reservoir as a means of storing raw water and conserving water resources and threatening the sustainability of the Julantoro reservoir. This study aims to determine the valuation of the embung julantoro ecosystem services by calculating the economic valuation of the embung with a scenario of fishery cultivation and tourism so that the value obtained becomes the basis for policies to improve the quality of the embung julantoro ecosystem services. This study uses two approaches, namely the Market Based Valuation Method to calculate the value of aquaculture ecosystem services and the Contingent Valuation Method to calculate the value of recreational ecosystem services using Willingness To Pay (WTP) analysis. The results of this study are the value of freshwater aquaculture ecosystem services of Rp. 938,001,330, then the value of recreational ecosystem services is Rp. 59.272.835.242 with a mean WTP value of 7.721,52, so that the total economic value is IDR 60.210.836.572, with the greatest benefit value from recreational ecosystem services. The large value of recreational ecosystem services indicates that the Julantoro reservoir has the potential to be developed into a recreation area because it provides large economic benefits.